4CPS-263 Reduction of potentially inappropriate prescriptions at discharge in a population of nonagenarians. (2nd March 2018) - Gemma, PC; Mònica, GV; Ricard, CM; Antonia, VM Maria; Paula, MA; Alba, PC; Molas, G; Sara, OR
Abstract : Background: The number of nonagenarians has risen as the consequence of increased life expectancy. This fact forces us to analyse their pathophysiological characteristics and the mortality risks associated with this aged group. Impaired capacity for instrumental and daily activities, cognitive decline, comorbidity and polypharmacy has shown to increase that risk. Polypharmacy (>4 chronic drugs) in elderly people is related to an increase in drug-related problems (DRP) and worse health outcomes due to the high number of potentially inappropriate prescriptions (PIP). Purpose: To describe demographic and clinical characteristics of nonagenarian patients and their pharmacological treatment. To evaluate the differences in chronic treatment and PIP in nonagenarian patients between admission and discharge. Material and methods: We included ≥90 years-old patients with polypharmacy discharged between January and June of 2017 from an Acute Geriatric Unit (81 beds) of a Geriatric Healthcare Centre from a University Hospital. Registered variables: age, sex, Barthel Index and Pfeiffer Test before admission. Number of chronic drugs/patient, number of PIP/patient and chronic benzodiazepines use before admission and at discharge. Pharmacist interventions due to DRP; length of stay (LOS) and mortality. Data are presented as median (Q1–Q3). We use Fisher's exact test for qualitative and the Mann–Whitney U test and the Wilcoxon signed-rank test for quantitative data. Statistical analysis was performed with Stata 13. One hundred and eighteen patients included: Age 92 (90–94). Females 78 (66.1%). Data at admission: Barthel Index 50 (35–75); Pfeiffer Test three (1–7). Chronic drugs/patient 10 (7–13). Average of PIP/patient 1.1 (±0. 88). Pharmacist interventions due to DRP: indication 12 (10.2%) patients; effectivity 16 (13.6%); safety 5 (4.2%); advice to nursing five (4.2); others 16 (13.6%). LOS nine (6–15) days. Mortality 38 (32.2%) patients. Differences between admission and discharge (n=80): chronic drugs/patient 10 (8–14) vs 11 (7–15), p=0.192; PIP/patient (average ±SD) 1.14 (±0.85) vs 0.84 (±0.81), p≤0.001; chronic benzodiazepines use 30 (37.5%) vs 15 (18.8%), p≤0. 001. Conclusion: The nonagenarian patients presented mild cognitive impairment, severe dependence and high polypharmacy. The majority of pharmacist interventions were related to effectivity, such as, renal impairment–associated drug dosage adjustment. At discharge, the number of chronic drugs prescribed increased but the PIP and use of benzodiazepines significantly decreased. References and/or Acknowledgements: All medical and nursing staff of Geriatric Healthcare Centre. No conflict of interest